134 Research and design for cardiac perfusion – visualisation of data 'quality markers'. (December 2018) - Aiyer, S; Issit, R; Rogers, Y; Sebire, NJ
Abstract : Background: Managing content for internal communication purposes remains suboptimal, particularly regarding ease of users' ability to rapidly upload and publish new content. The aim of this study was to create a portal content management system to allow rapid, easy content deployment for use initially in the digital research and informatics unit (DRIVE) at GOSH as a proof of principle. Methods: We developed an interactive events website and 'kiosk' app to allow rapidly updated information to be displayed both on the website and on check-in kiosks deployed across the hospital. For the kiosk app, we used Ruby on Rails, for the events website we used PHP (and related technologies such as HTML, CSS) with MySQL hosted on Azure. Results: We demonstrate a working prototype of the events website and content delivery 'kiosk' app. We included stripe API functionality that allows users to pay for events, informing them if the transaction was successful. The email address of people that successfully booked for an event is stored in the database and can be seen from the Administrator Page, so that the admin knows how many have booked. For the kiosk an administrator has control over which posts are displayed. They can create, edit or delete posts and can create other users and departments. A live social media feed displaying tweets from the official Great Ormond Street twitter account was added by embedding HTML. Conclusion: Further work is required to add functionality such as when a user books for an event, an email with QR codes is sent. The kiosk app and website should share the same database, so that each time an event was added from the website, it would be displayed on the kiosk app simultaneously without having the need to modify it on both systems. Testing is required to determine high volume data flow.